IN VITRO MASS PROPAGATION AND SYNTHETIC SEED PRODUCTION COMBINED WITH PHYTOCHEMICAL AND ANTIOXIDANT ANALYSIS OF BACOPA CHAMAEDRYOIDES: AN ETHNO-MEDICINALLY IMPORTANT PLANT - Haque, Sk Moquammel; Kundu, Subrata; Das, Anupam; Ghosh, Biswajit (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: This study was carried out to optimize adventitious shoot buds induction from the surface of the leaf and internode explants along with investigation of the phytochemical constituents and in vitro antioxidant potential of aerial parts of Bacopa chamaedryoides, an ethno-medicinally important plant. Methods: All the analysis was performed according to standard protocols. Results: Maximum 26.3Â±05 shoots per leaf explant and 32.3Â±0.41 shoots per internode explants were induced on MS basal medium supplemented with 3.0 mg/L TDZ and 15% Aloe vera gel (AvG) fortified fortified medium within 30-32 days. Multiplied shoots were successfully rooted with maximum 16.8Â±0.35 root per shoot on half strength MS medium supplemented with 50% of AvG and reached 2.1Â±0.24 cm length within 15 days. Finally, the rooted plants were hardened and transferred to soil with 87.8% success rate. Micro-shoots were encapsulated in calcium alginate beads for the production of synthetic seeds (SSs). The best result was observed in 3.0% sodium alginate by means of proper globular shaping of SSs with 90.0% germination rate. The ethanolic extracts were evaluated for their potential antioxidant activities using different in vitro systems and exhibit better scavenging activity of 2,2-diphenyl-1-picrylhydrazyl (IC50 = 1150.446 Î¼g/mL), 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (IC50 = 13.781 Î¼g/mL) and ferric reducing antioxidant power (IC50=5.663 Î¼g/mL). High-performance thin layer chromatography was performed to corroborate the biochemical analysis of antioxidant activity. Conclusion: The results of this study indicate that the aerial part of B. chamaedryoides is a valuable source of Â Â